Targeting the anti-apoptotic BCL-2 family members for the treatment of cancer - Weyhenmeyer, B.; Murphy, A.C.; Prehn, J.H.M.; Murphy, B.M. (Experimental Oncology, 2012)
Most cells express a variety of both anti-apoptotic and pro-apoptotic Bcl-2 proteins and the interaction within this family dictates whether a cell survives or dies. The dysregulation of the anti-anti-apoptotic Bcl-2 family members is one of the defining features of cancer cells in comparison to normal cells, and significantly contributes to the resistance of cancer cells to current treatment modalities. This anti-apoptotic subfamily of proteins is now a major target in the development of new methods to improve treatment outcomes for cancer patients. Several drugs directed at inhibiting Bcl-2 and related anti-apoptotic proteins have been developed with some showing considerable promise in the clinic. This Review presents the current knowledge of the role of the anti-apoptotic Bcl-2 family in cancer cells, as well as current and future perspectives on targeting this subfamily of proteins for therapeutic intervention in human malignancies. This article is part of a Special Issue entitled “Apoptosis: Four Decades Later”.